(untitled) (Research, Society and Development, 2022)
The objective of the research was to quantify the levels of noise and carbon dioxide (CO2) to which people are exposed to punctually or more continuously. Data collection was performed at 5 points in the city of Campina Grande, namely: the passenger integration terminal and the bus station, the Federal University of Campina Grande, the children’s park and Maciel Pinheiro Street located downtown. Data collection took place from 10 am to 11:30 am, with one day in each location. The methodology adopted to evaluate the noise levels was based on NBR 10.151/2000, and the results were compared to the environmental legislation and the State Decree 15.357/1993, which set the conditions of acceptability. As for the concentration of CO2, the results obtained were compared to the values set in NR-15, Annex 11. The results showed that the Passenger Integration Terminal has more critical values regarding the noise issue, obtaining an average level of 75.17 dB, justified by the higher vehicle flow among the analyzed points. The Federal University of Campina Grande presented a more comfortable situation regarding sound pressure, being, therefore, in accordance with the current legislation. The CO2 concentrations did not present values harmful to human health, as well as to the environment in all sites analyzed. As for noise pollution, it is recommended that urban planning be carried out using shrub species that will act as natural barriers, together with monitoring by the competent bodies to curb abusive noise practices by some local businesses.